(untitled) (Research, Society and Development, 2021)
Objective: Debate on the therapies most used in pregnant women with MDD and analyze the postpartum implications, in addition to the risks and benefits of the drugs of choice. Methodology: Integrative literature review, using articles from the academic platforms SciELO, PuBMED, MEDLINE and Science Direct, considering an interval between 2016-2021, that addressed the subject of pharmacological therapy with Selective Serotonin Reuptake Inhibitors (SSRIs) and/or Serotonin Norepinephrine Reuptake Inhibitors (SNRIs) in the gestational period or non-adherence to treatment, with a finding of 12 articles that met the inclusion and exclusion criteria. Results: Most studies support the effectiveness of treatment with SSRIs and/or SNRIs in pregnant women, but there is difficulty in developing a plan with the lowest possible risk, because the drugs with the best results also present a certain degree of risk. These same studies, as well as others, highlight the teratogenic effects and some other findings during treatments with SSRIs and/or SNRIs and, in case of non-treatment, the effects of depression throughout pregnancy. Some of the findings indicate adherence to co-treatment using non-pharmacological therapies, such as psychotherapy (recommended by guidelines as the ideal initial treatment in mild to moderate cases), associated with pharmacological therapy. Conclusions: It can be concluded that there are studies on the benefits and harms of the use of antidepressants during pregnancy, in such a way that it is difficult to define the best strategy, it being up to professionals to define cost-benefit according to each patient and situation.